Kepribadian Ekstrofet Tokoh Dalam Novel Pudarnya Pesona Cleopatra Karya Habiburrahman El-Shiarzy Kajian Psikoanalisis - Maftuhah (Jurnal Pendidikan Islam, 2020)
Abstract: This research describes a personality of a character'sextrofet which is implied by the study of psychoanalysis put forward bySigmund Freud in Habiburrahman El-Shirazy's Faded PesonaCleopatra novel. The problems that the writer will study are: 1. Howare the personality forms of the character's extrofet in the novelPudarnya Pesona Cleopatra by habiburrahman el-shirazy whichincludes (1) the main character or I, (2) the raihana character or wifeof the main character, (3) the mother character , (4) the figure ofyaqulbi, and (5) the figure of yasmin or the wife of yaqulbi and 2. Howis the personality description of the character's extrophette based onthe psychoanalytic study of Sigmund Freud in the novel PudarnyaPesona Cleopatra by Habiburrahman El-Shiarzy. Research conductedon the novel Fading Pesona Cleopatra results in that in all activities oflife the personality of a character is always based on three principlesas said by Sigmund Freud namely Id, Ego, and Super Ego. These threeprinciples are the principle of constant, pleasure principle and thereality principle contained in human life